2015
DOI: 10.1017/s2040174415001336
|View full text |Cite
|
Sign up to set email alerts
|

Fetal sex differences in human chorionic gonadotropin fluctuate by maternal race, age, weight and by gestational age

Abstract: Circulating levels of the placental glycoprotein hormone human chorionic gonadotropin (hCG) are higher in women carrying female v. male fetuses; yet, the significance of this difference with respect to maternal factors, environmental exposures and neonatal outcomes is unknown. As a first step in evaluating the biologic and clinical significance of sex differences in hCG, we conducted a population-level analysis to assess its stability across subgroups. Subjects were women carrying singleton pregnancies who par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 41 publications
(55 reference statements)
2
21
1
Order By: Relevance
“…Sex and gestational variation in hCG have been previously established at the population level in analyses of hCG biomarker data ( Adibi et al 2015b ; Bremme and Eneroth 1983 ; Buckberry et al 2014 ; Clements et al 1976 ; Cowans et al 2009 ; Nagy et al 1994a , 1994b ; Steier et al 1999 ; Yaron et al 2002a ). This type of variation is generally not considered when analyzing in vitro experimental data.…”
Section: Discussionmentioning
confidence: 99%
“…Sex and gestational variation in hCG have been previously established at the population level in analyses of hCG biomarker data ( Adibi et al 2015b ; Bremme and Eneroth 1983 ; Buckberry et al 2014 ; Clements et al 1976 ; Cowans et al 2009 ; Nagy et al 1994a , 1994b ; Steier et al 1999 ; Yaron et al 2002a ). This type of variation is generally not considered when analyzing in vitro experimental data.…”
Section: Discussionmentioning
confidence: 99%
“…Yaron et al reported that in patients who underwent to ART procedures, from the 14th and the 20th day post-fertilization, women attending a female fetus had higher levels of hCG than women attending a male ( p < 0.002) [10]. Adibi et al also found a significantly higher hCG level ( p < 0.0001) in patients with a female fetus rather than patients with a male fetus both during the first and the second trimester on a wide population (1.1 million) of women subjected to screening [11]. The results of our study are mostly in line with those reports, and, more specifically, we did not find any difference in hCG serum levels until the seventh week of pregnancy, but the values of female fetuses were significantly higher between 11 and 13 gestational weeks.…”
Section: Discussionmentioning
confidence: 99%
“…One of the factors that most influences the bio-humoral condition of the first weeks of pregnancy seem to be the fetal sex and, specifically, women with female fetus may present higher values of hCG compared to male fetuses [10, 11].…”
Section: Introductionmentioning
confidence: 99%
“…During gestation, the biochemical indicators in maternal serum that show fetal/placental sex-dependent variation in concentrations include human chorionic gonadotropin (hCG) 26 , soluble fms-like tyrosine kinase-1 (sFlt-1) 27 and placental alkaline phosphatase (PLAP) 28 . These placental proteins and angiogenic factors show elevated levels in maternal serum of healthy female pregnancies compared to male pregnancies.…”
Section: Introductionmentioning
confidence: 99%
“…From gene expression studies it is known that the tissues of the placentas do have tissue specific sexually different gene expression patterns (“sexomes”) 33 . Spotting the site of sexual dimorphism is thus essential to reliably connect the genetic 16 , biochemical (placental proteins) 2628 and gross morphological (placental weight and birthweight) 17,18 sex-specific differences of human placentas to a functional picture by anchoring them to a structure/tissue.…”
Section: Introductionmentioning
confidence: 99%